Exhaled nitric oxide is a good, non-invasive test for steroid responsive airways disease in elite swimmers - Martin, N.; Lindley, M. R.; Hargadon, B.; Monteiro, W.; Pavord, I. D. (Journal of Sports Science & Medicine, 2012)
Asthma is common in elite level swimmers. With the change in WADA testing rules there is no longer a requirement for elite level athletes to have objective airways testing. There is marked heterogeneity in athletes and knowing which athletes are likely to respond to inhaled corticosteroids allows for targeted therapy. As part of a larger study looking at airways disease in symptomatic elite level athletes, we compared the effectiveness of the cheap, quick, non-invasive measurement of exhaled nitric oxide against induced sputum eosinophil percentage counts and response to standard eucapnic voluntary hyperventilation (EVH) testing. Methods: Athletes were inhaled corticosteroid naïve or stopped steroids for 4 weeks prior to testing. All of the athletes had symptoms suggestive of exercise asthma. They had baseline exhaled nitric oxide, spirometry, EVH and then induced sputum carried out using our standard research protocols. Results: A total of 80 elite level swimmers took part in the study. Of these 27 had a sputum eosinophil count of >3% (34%) and of these 26 (96%) had a drop in FEV1 after EVH of >10%. Of the 53 (66%) of swimmers with a sputum eosinophil count of <3% only 24 had a positive EVH test (45%). When comparing the levels of measured FENO to sputum eosinophilia an FENO of >43 had the best predictive value. (ROC: AUC = 0.93, p < 0.0001, sens: 88.46%, spec: 96.23%). Conclusions: A sputum eosinophil count of >3% is the most robust marker of steroid responsiveness in asthma. Swimmers with this level of disease have positive EVH tests and an elevated FENO. FENO is an excellent noninvasive, cheap, pool side test that can be used to screen symptomatic elite level swimmers for steroid responsive airways inflammation.